Free and Equal : Rawls' Theory of Justice and Political Reform. - Grcic, Joseph (Algora Pub., 2011)
The ideas of John Rawls have revolutionized the shape and content of much of contemporary political and social philosophy. His A Theory of Justice (1971) and Political Liberalism, (1993) among other works, have been a rich source of ideas which continue to influence contemporary discussions about justice and politics. Although much has been written on the political philosophy of Rawls, there has not been any in-depth study focused on the implications of the ideas of Rawls for contemporary existing democracies. Drawing on some of his earlier work, the author offers a detailed exploration of ho.